(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This research was conducted to complement research on student violence based on cases in developing countries. The complexity of the problem in developing countries, coupled with the condition of Indonesia as a multicultural country with differences in ethnicity, religion, and culture, makes Indonesia prone to conflict. This research was conducted to analyze the problem and find the right solution to overcome student violence. This research was conducted at two universities in Makassar City using qualitative research methods. Data was collected through in-depth interviews. The results showed that the reorientation of local values became something urgent to be solved. It is because of differences in the character of students, organizational flags, and tribes, such as time bombs, that can explode at any time just because of differences. The results of this study are expected to be a strategy to overcome student violence in multicultural countries such as Indonesia by strengthening national values Bhinneka Tunggal Ika.